Validity and reliability of dryland, flexibility and visualization (DFV) training model to improve butterfly swimming - Nur Indah Pangastuti; Fx. Sugiyanto; Devi Tirtawirya (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2026)
The training model used so far is still partial, such as the separation between physical, technical, and mental training. This study conducted a study on the combination of physical and mental training with the abbreviation DFV (Dryland, Flexibility, Visualization) training model. The purpose of the study was to develop and assess the validity and reliability of the DFV training model with the imposition of improving butterfly swimming technique skills on beginner swimmers aged 10-11 years. A total of seven experts were asked to assess 17 movement items of the DFV training model. The seven experts were divided into three theorists and four professional swimming coaches. Data were collected using the Delphi technique and then analyzed using the Aiken formula for validity and Cronbach's alpha for reliability. The results obtained in the Aikens test were 0.899. Based on the Aiken's table value with seven expert validators is 0.86, so it can be concluded that the movement items of the DFV Exercise model are valid with a significance level of 0.07. Cronbach's alpha is used to measure the reliability of each aspect of the DFV exercise model instrument, with the result of 0.833 which is greater than the alpha value (0.6) then it can be said that this exercise model is reliable. Based on the results of the calculation of the validity and reliability values, it shows that this DFV exercise model can be continued for further development. The implications of this study can prove that the DFV exercise model can be used to improve butterfly swimming skills in beginner athletes aged 10-11 years which can be used for coaches and in physical education teaching.